Adaptive RD Optimized Hybrid Sound Coding - van Schijndel, Nicolle H.; Bensa, Julien; Christensen, Mads Graesboll; Colomes, Catherine; Edler, Bernd; Heusdens, Richard R.; Jensen, Jesper Højvang; Jensen, Søren Holdt; Kleijn, B.; Kot, Valery S.; Kövesi, Balázs; Lindblom, Jonas; et al. (Journal of the Audio Engineering Society, 2008)
Traditionally, sound codecs have been developed with a particular application in mind, their performance being optimized for specific types of input signals, such as speech or audio (music), and application constraints, such as low bit rate, high quality, or low delay. There is, however, an increasing need for more generic sound codecs, created by the emergence of heterogeneous networks and the convergence of communication and entertainment devices. To obtain such versatility, this study employs hybrid sound coding based on operational rate-distortion (RD) optimization principles. Applying this concept, a prototype coder has been implemented with emphasis on (dynamic) adaptation to the input and to application constraints. With this prototype, listening tests have been performed for different application scenarios. The results demonstrate the versatility of the concept while keeping competitive sound quality compared to dedicated state-of-the-art codecs.
UnivIS-Import:2015-04-20:Pub.2008.tech.IE.aulab.zentr.adapti